Doubles and mirrors: Two Flannery O’Connor stories about race relations - Buchholtz, Mirosława (Litteraria Copernicana, 2025)
This article examines the depiction of racial relations in two short stories by Flannery O’Connor against the backdrop of sociopolitical changes in the mid-20th-century United States. It is often assumed that, because O’Connor occasionally expressed racist views in her letters, her fiction is also tainted by racism. However, a close reading of two of her short stories, The Artificial Nigger (1955) and Everything That Rises Must Converge (1961), reveals an entirely different agenda. This article seeks to demonstrate that O’Connor provoked her white readers and undermined white supremacy in her fiction. Thus, one could argue that, by exposing the prejudice and hypocrisy of white people, her stories supported the cause of the civil rights movement. By studying these two stories, I juxtapose O’Connor’s portrayal of two different types of characters and settings and two distinct historical moments: rural versus urban perspectives on racial issues before and after the enactment of desegregation laws. Like many people in her social environment, O’Connor witnessed integration with mixed feelings, but her fiction transcends this disorientation.